Transcriptome sequencing of sesame (Sesamum indicum) using Illumina Platform - SUPRIYA, P; RAO, A R; BHAT, K V (The Indian Journal of Agricultural Sciences, 2023)
Sesame is an important oil seed crop worldwide and has essential health and medicinal values. In the present study, ahigh-throughput transcriptome sequencing of sesame was performed using Illumina paired-end sequencing technologyfor gene and marker discovery. Approximately 6 Gb data was generated and assembled into 16548 unigenes withan N50 of 905 bp. In addition, a total of 1716 unigeneswere assigned to 22 KEGG pathways. The unigenes resultedfrom this study are involved in lipid metabolism and Glycan biosynthesis pathways etc. Furthermore, 1443 SimpleSequence Repeats (SSR) were detected and consequently primers were designed.Our study enhances the genomic resources of sesame and provides ample amount of information about the transcriptome and SSRs which could serveas a valuable basis for future studies.